Genotoxic Response and Mortality in 3 Marine Copepods Exposed to Waterborne Copper. (24th September 2019) - Sahlmann, Andrea; Lode, Torben; Heuschele, Jan; Borgå, Katrine; Titelman, Josefin; Hylland, Ketil
Abstract: Copper (Cu) is an essential trace metal, but may also be toxic to aquatic organisms. Although many studies have investigated the cytotoxicity of Cu, little is known about the in vivo genotoxic potential of Cu in marine invertebrates. We investigated the genotoxicity of Cu in 2 pelagic calanoid copepods, Acartia tonsa and Temora longicornis, and the intertidal harpacticoid copepod Tigriopus brevicornis by exposing them for 6 and 72 h to waterborne Cu (0, 6, and 60 µg Cu/L). A subsequent 24‐h period in filtered seawater was used to investigate delayed effects or recovery. Genotoxicity was evaluated as DNA strand breaks in individual copepods using the comet assay. Copper did not increase DNA strand breaks in any of the species at any concentration or time point. The treatment did, however, cause 100% mortality in A. tonsa following exposure to 60 µg Cu/L. Acartia tonsa and T. longicornis were more susceptible to Cu‐induced mortality than the benthic harpacticoid T. brevicornis, which appeared to be unaffected by the treatments. The results show major differences in Cu susceptibility among the 3 copepods and also that acute toxicity of Cu to A. tonsa is not directly associated with genotoxicity. We also show that the comet assay can be used to quantify genotoxicity in individual copepods. Environ Toxicol Chem 2019;38:2224–2232. © 2019 SETAC. Abstract : Exposure of 3 marine copepods to waterborne Cu with genotoxicity measured as DNA strand breaks in individual copepods (comet assay) and mortality as end points. Acute toxicity, observed as mortality in Acartia tonsa, was not directly linked to DNA strand breaks.